The Supreme Court and the Conventions of the Constitution - Sirota, L (LexisNexis Canada, 2017)
Conventions are among the most important rules of the Canadian constitution. Yet orthodox legal theory does not recognize them as being rules of law, a view which the Supreme Court of Canada endorsed in the Patriation Reference. Nevertheless, both before and after the Patriation Reference, the Court's jurisprudence engaged with existing or alleged constitutional conventions. This article reviews this jurisprudence, and the scholarly commentary that responded to it. It concludes that the Court's endorsement of the orthodox view that there exists a rigid separation between conventions and law was poorly justified, and ought to be abandoned.
Keywords: Constitutional conventions; Canada; Dicey; Patriation Reference